KEADILAN ELEKTORAL BAGI PEMILIH PENYANDANG DISABILITAS MENTAL PADA PEMILU SERENTAK 2019 DI SURABAYA - Nikita Desverose; Priyatmoko Priyatmoko (Universitas Airlangga, 2020)
This research focuses on upholding political justice in elections for mentally disabled people, more precisely about how the state and its institutions seek to restore political rights and implement inclusive election policies for person with mental disabilities regarding their participation in elections and their right to vote when election. This research takes two main topics, namely restoration of political rights of mentally disabled people in elections through the regulation of the Election Law, and the making of special rules to accommodate the needs of mental disabled people in elections and the implementation of these policies in the 2019 elections in the city of Surabaya. Data obtained through the analysis of news content and interviews with sources that are then processed and explained qualitatively descriptive. The theory used in this research is electoral justice theory, with a focus on conformity in the field with elements of justice in the electoral justice system. The results obtained are in the first part, the regulation carried out by the government based on complaints from community organizations that focus on defending mental disability rights and electoral issues, meets the criteria for fulfilling rights and distributing justice first where the state gives equal rights for everyone to channel their voice in elections, without discriminating any group by giving them access to the right to be registered as DPT and entitled to participate in the election process. In the second part, it discussed the implementation of the policy in the city of Surabaya, specifically at the Menur Hospital and found that the state tried to accommodate the political rights of the mentally disabled in elections by providing more specific technical rules by adjusting the conditions and needs of the mentally disabled, which according to the elements election justice which requires electoral governance to protect citizens' voting rights. The final conclusion of this study illustrates how the state and its institutions fulfill the elements of the electoral justice system in distributing justice in elections, for people with mental disabilities in Indonesia, especially in the city of Surabaya in the 2019 Elections.